RENAL VEIN THROMBOSIS AT HIGH ALTITUDE - Abdul Rehman Arshad; Farrukh Islam; Mohsin Qayyum (Pakistan Armed Forces Medical Journal, 2021)
Though risk of venous thromboembolism in increased at high altitude, involvement of renal veins is rare. A 27-year-old soldier was evacuated from a height of 18000 feet after developing flank pain and haematuria. Ultrasound showed an enlarged left kidney and lack of flow in proximal renal vein. CT scan confirmed the presence of renal vein thrombus. Serum IgM Anti β-2 Glycoprotein I antibodies, IgG Anti β-2 Glycoprotein I antibodies and IgM anticardiolipin antibodies were detectable and the former two were present after three months also. Secondary causes of antiphospholipid syndrome were excluded. He was started on low molecular weight heparin and is now on lifelong oral anticoagulation with warfarin.